Changes in joint, muscle, and tendon stiffness following repeated hopping exercise - Kubo, Keitaro (Physiol Rep, 2019)
The purpose of this study was to elucidate the mechanisms of decline in joint stiffness after repeated stretch‐shortening cycle exercises according to changes in both muscle‐tendon properties and neuromuscular activities. Eleven males performed fatigue task (5 sets of 50 hopping). Ankle joint stiffness and electromyographic activities (mEMG) of plantar flexor and tibial anterior muscles during drop jump were measured before and after fatigue task. Active muscle stiffness with (100 deg·sec(−1)) and without (250 deg·sec(−1)) stretch reflex were calculated according to changes in estimated muscle force and fascicle length during fast stretching after submaximal isometric contractions. Tendon stiffness was measured during ramp and ballistic contractions. After fatigue task, joint stiffness significantly decreased by 20.7 %, whereas mEMG of measured muscles during drop jump did not. After fatigue task, active muscle stiffness with and without stretch reflex significantly decreased by 15.7 % and 21.5 %, and tendon stiffness measured during ramp and ballistic contractions did not change. In addition, the relative change in joint stiffness was significantly correlated with that in active muscle stiffness with stretch reflex (r = 0.737, P = 0.009), but not with those in the other measured variables. These results suggested that the decline in joint stiffness after repeated hopping exercises would be caused by changes in active muscle stiffness, but not those in tendon properties or neuromuscular activities.